ONS-5010 (bevacizumab-vikg) Safety and Efficacy in Subfoveal Choroidal Neovascularization Secondary to Age-related Macular Degeneration - Rahhal, Firas M (Ophthalmic surgery, lasers & imaging retina, 2024)
BACKGROUND AND OBJECTIVE: This was a prospective multicenter, randomized, double-masked, active-controlled study, the aim of which was to demonstrate the efficacy and safety of intravitreal ONS-5010 (bevacizumab-vikg) in eyes with neovascular age-related macular degeneration (nAMD). This was a phase III trial on ONS-5010 (NORSE TWO)